Analysis of Rock Bolt Behaviour under Shear and Combined Load and an Improved Rock Bolt Design Methodology - Pinazzi da Silva Ribeiro, Pammela Caroline (Curtin University, 2019)
Rockbolts are subjected to different tensile and shear loads along their length that change with mining. Common rockbolt design methodologies, however, assume that they are loaded in tension only (the most common design assumption) or pure shear. Laboratory tests were conducted with rockbolts under different loading conditions including both tensile and shear together. From the results, a new methodology is proposed where the tensile capacity is reduced by 50% as this accounts for most loading scenarios.